Vitamin A-biofortified maize: Exploiting native genetic variation for nutrient enrichment - Menkir, Abebe; Palacios-Rojas, Natalia; Alamu, Oladeji; Dias Paes, Maria Cristina; Andersson, Meike S.; Bouis, Howarth E.; Jamora, Nelissa; Major, Michael (Crop Trust, 2018)
Vitamin A is important in immune function. Approximately one third of children under the age of five are at risk for Vitamin A deficiency (WHO 2009). This is the leading cause of preventable childhood blindness. Nutrition trials in countries administering Vitamin A capsules resulted on average in a 24% reduction in child mortality. By breeding staple crops with higher amounts of Vitamin A, the supply of Vitamin A in our food sources can be sustainably increased. Maize provides approximately 30% of the total calories of more than 4.5 billion people in developing countries, and is the most widely eaten food staple in Africa. Poor quality diets, dominated by food staples, are often deficient in minerals and vitamins, but maize can provide sufficient quantities of Provitamin A (proVA), which the body converts to Vitamin A. Maize can grow in diverse environments and has a high potential to be bred to provide productive cultivars that are attractive to farmers and consumers, including for their nutritional properties. HarvestPlus has collaborated with CIMMYT, IITA, EMBRAPA and other partners to develop maize varieties that are high yielding, profitable, acceptable to consumers, and also rich in Provitamin A carotenoids (Box 1). Beta-carotene is the most common proVA carotenoid in plants. The breeding target for maize was set at 15 µg/g of beta-carotene, to provide an additional 50% of the estimated average requirement for Vitamin A in maize-eating regions. Maize with these levels of beta-carotene would be an effective contributor to reducing Vitamin A deficiency.